Analysis of Needs for the Application of Differentiated Learning in Class X Natural and Social Sciences Subjects at SMKN 1 Bengkulu City - Rosni, Rosni (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2023)
The research aims to find out how the implementation of learning is differentiated in class X natural and social sciences at SMKN 1 Bengkulu City even semester of the 2022-2023 academic year. In this study, a qualitative approach is combined with a descriptive way of analysis. The study's findings are displayed in the form of exposure. The data collection methods used in this study were observation, interviewing, and documentation. There were 5 participants in the study at SMKN 1 Bengkulu City. This study's main objective is to describe how differentiated learning can be implemented in the solar system's natural and social sciences chapter. In the first phase, learning readiness, interests, and learning profiles are used to map students' learning needs. The second phase is to plan, which entails developing a differentiated learning strategy employing three types of differentiation: content, process, and product.  The third phase involves implementing differentiated learning in accordance with the created learning implementation plan, and the fourth phase involves evaluation and reflection with the goal of being able to perceive the drawbacks and benefits as material for the next learning improvement. Researchers are interested in the effects of differentiated learning implementation on classroom learning activities once it has been put into place. From the results of the interviews, it was concluded that 85% of the science teachers at SMKN 1 Bengkulu City agreed, the school management team 100% agreed, and 98% of students agreed to apply differentiated learning to the science subject in class X SMKN 1 Bengkulu City.